Leituras sobre expressões hoteleiras em Santa Maria (1882-1930) - Santos, Nastaja Cassandra Zamberlan dos (2019)
In 1885, with the arrival of the rails in the city of Santa Maria RS, the economic and social scenario began a new reality. Due to its geographical position, Santa Maria became a reference, acting as a place for people buying and traveling. Considered an important railway track, the railway station was responsible for the core of the urban movement. From this context, this dissertation aims to verify, through a historical, documentary and photographic approach, the hotel developments in the period related to the end of the 19th century and beginning of the 20th century. The creation of a blog as a Professional Master’s Degree product, corroborates the rescue of memories and identities of the city. As specific objectives, this study aimed the identification of the main hotels in the period corresponding to 1882 to 1930, as well as their location, period of ascension and end of these means of lodging. The methodology consisted of researches in newspapers of the time, as well books on local history. Another instrument used was oral history, a tool of great importance in the research, in which testimonies of former railway historians and other interviewees recall the past of the city through semi-structured interviews. In addition, snowball sampling was used, in which interviews with social actors whose characteristic is the initial participants indicate new participants, which, in turn, indicate new participants and so on until it is reached the proposed goal – the “saturation point” –, that is reached when the new interviewees begin to repeat the contents already obtained in previous interviews, without adding new relevant information. Based on theoretical references such as Cultural Patrimony, Tourism and Hospitality, Memory and Hospitality, this study proposes to be a remembrance exercise to identify and map the old hotels of Santa Maria, a city located in the Central Region of RS. Eventually, a blog (product) was prepared to offer cultural information retrieved in the study, distributed in small posts and supported with photographs.